PREDIKSI FINANCIAL DISTRESS MELALUI METODE ALTMAN Z-SCORE MODIFIKASI DAN ANALISIS POLA ARUS KAS: STUDI KASUS PT WASKITA KARYA (PERSERO) TBK PERIODE 2018-2024 - Annisa Nurhamidah (Jurnal Akuntansi Kompetif, 2026)
This research aims to predict bankruptcy from PT Waskita Karya (Persero) Tbk from the year 2018-2024. Case study method with a quantitative approach was used in the research. Data analysis tools uses Microsoft Excel with Altman’s Z-Score Modificated model and cash flow patterns. The Altman’s Z-Score uses financial ratios that are Working Capital to Total Assets, Retained Earnings to Total Assets, Earning Before Interest and Taxes to Total Assets, and Book Value of Equity to Total Liability. The results showed company’s categories include grey zone and distress. Analysis Altman’s Z-Score is strengthened using the cash flow pattern and shows that the company is at the financial difficulties or bankruptcy. Keywords: Bankruptcy prediction, Altman’s Z-Score modificated, Cash flow patterns